A New Tessera into the Interactome of the isc Operon: A Novel Interaction between HscB and IscS - Puglisi, Rita; Yan, Robert; Adinolfi, Salvatore; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2016)
Iron sulfur clusters are essential universal prosthetic groups which can be formed inorganically but, in biology, are bound to proteins and produced enzymatically. Most of the components of the machine that produces the clusters are conserved throughout evolution. In bacteria, they are encoded in the isc operon. Previous reports provide information on the role of specific components but a clear picture of how the whole machine works is still missing. We have carried out a study of the effects of the co-chaperone HscB from the model system E. coli. We document a previously undetected weak interaction between the chaperone HscB and the desulfurase IscS, one of the two main players of the machine. The binding site involves a region of HscB in the longer stem of the approximately L-shaped molecules, whereas the interacting surface of IscS overlaps with the surface previously involved in binding other proteins, such as ferredoxin and frataxin. Our findings provide an entirely new perspective to our comprehension of the role of HscB and propose this protein as a component of the IscS complex.